Impacts of the COVID-19 pandemic on livelihoods and wild meat use in communities surrounding the Dja Faunal Reserve, South-East Cameroon - Kamogne Tagne, C.T.; Brittain, S.; Booker, F.; Challender, D.W.S.; Maddison, N.; Milner-Gulland, E.J.; Mouamfon, M.; Roe, D.; Coad, L.M. (Wiley, 2022)
The COVID-19 outbreak has had considerable negative impacts on the livelihoods and living conditions of communities around the world. Although the source of COVID-19 is still unknown, a widely spread hypothesis is that the virus could be of animal origin. Wild meat is used by rural communities as a source of income and food, and it has been hypothesised that the pandemic might alter their perceptions and use of wild meat. McNamara et al. (2020) developed a causal model hypothesising how the impacts of the pandemic could lead to a change in local incentives for wild meat hunting in sub-Saharan African countries. From February 27 to March 19, 2021, we carried out a survey around the Dja Faunal Reserve, Southeast Cameroon, to test McNamara et al.’s model in practice, using semi-structured questionnaires to investigate the impacts of the COVID-19 outbreak on wild meat hunting and consumption. Our results generally agree with the causal pathways suggested by McNamara et al. However, our study highlights additional impact pathways not identified in the model. We provide revisions to McNamara's model to incorporate these pathways and inform strategies to mitigate the impacts of the pandemic.